Perioperative nursing of transcatheter aortic valve replacement (经导管主动脉瓣置换术围术期护理配合) - LU Jianfa (卢建发); HE Jing (贺菁); WANG Xiaoping (王晓萍); HUANG Zhuqiu (黄槠萩) (Association of Integrative Nursing, 2022)
Transcatheter aortic valve replacement (TAVR) is a multidisciplinary collaborative procedure in which close coordination between the doctor and nursing care is the key. This article summarized the experience of perioperative nursing of TAVR, and provided reference for guiding the clinical practice. (经导管主动脉瓣置换术(TAVR)是一种多学科合作的手术, 医生和护理密切的配合是手术成功的关键。本文总结TAVR术前护理准备、术中配合及术后护理的围手术期护理经验, 以期为临床TAVR围术期的护理提供指导和参考。)